Innovation in Saudi Family SMEs: The Role of Social Capital and Family Involvement - Alrubaishi, Dalal; Robson, Paul (Senate Hall, 2019)
This study examines the influence of family business resources, represented by family involvement in management and social capital, on innovation outputs represented by incremental and radical innovation of products/services and processes. The results from a data set of 259 family firms in Saudi Arabia show that family firms that have a higher degree of family involvement and social capital are more likely to engage in incremental rather than radical innovation. Implications for research and practice are discussed in light of a context emphasizing the value of relationships and family reputation.
Keywords: innovation|family business|social capital|family involvement|Saudi Arabia